ICSI Does Not Improve Live Birth Rates but Yields Higher Cancellation Rates Than Conventional IVF in Unexplained Infertility - Song, Jianyuan; Liao, Tingting; Fu, Kaiyou; Xu, Jian (Frontiers in Medicine, 2021)
Objectives: Unexplained infertility has been one of the indications for utilization of intracytoplasmic sperm injection (ICSI). However, whether ICSI should be preferred to IVF for patients with unexplained infertility remains an open question. This study aims to determine if ICSI improves clinical outcomes over conventional in vitro fertilization (IVF) in couples with unexplained infertility. Methods: This was a retrospective cohort study of 549 IVF and 241 ICSI cycles for patients with unexplained infertility at a fertility center of a university hospital from January 2016 and December 2018. The live birth rate and clinical pregnancy rate were compared between the two groups. Other outcome measures included the implantation rate, miscarriage rate, and fertilization rate. Results: The live birth rate was 35.2% (172/488) in the IVF group and 33.3% (65/195) in ICSI group, P =0.635. The two groups also had similar clinical pregnancy rates, implantation rates and miscarriage rates. The fertilization rate of IVF group was significantly higher than that of ICSI group (53.8% vs 45.7%, P =0.000, respectively). 61 and 46 patients did not transfer fresh embryos in IVF and ICSI cycles, respectively. Patients with IVF had lower cancellation rates than those with ICSI (11.1% vs 19.1%, P =0.003, respectively). Conclusion: ICSI does not improve live birth rates but yields higher cancellation rates than conventional IVF in the treatment of unexplained infertility.